2020
DOI: 10.3390/metabo10090369
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Intracellular and Cell Wall-Bound Phlorotannin Fractions in Fucoid Algae Indicates Specific Functions of These Metabolites Dependent on the Chemical Structure

Abstract: Accumulation of biologically active metabolites is a specific feature of plant biochemistry, directing the use of plants in numerous applications in the pharmaceutical and food industries. Among these substances, the plethora of phenolic compounds has attracted particular interest among researchers. Here, we report on new findings in phlorotannin research, a large group of multifunctional phenolic substances, produced in brown algae. Comprehensive LC-MS profiling of three algal species allowed us to depict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 72 publications
(109 reference statements)
7
21
0
Order By: Relevance
“…However, our data ( Table 1 ) showed that most of the protein-rich red algae have a relatively low content of total carbohydrates (the only meaningful exception was R. confervoides ). A high amount of phenolics is mostly a problem of brown algae utilization, as they may contain up to 25% DW of specific polyphenols (phlorotannins) [ 41 ]. Red seaweeds typically contain lesser amounts of phenolic compounds than brown and green algae [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data ( Table 1 ) showed that most of the protein-rich red algae have a relatively low content of total carbohydrates (the only meaningful exception was R. confervoides ). A high amount of phenolics is mostly a problem of brown algae utilization, as they may contain up to 25% DW of specific polyphenols (phlorotannins) [ 41 ]. Red seaweeds typically contain lesser amounts of phenolic compounds than brown and green algae [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along temperate rocky shorelines fucoids typically dominate in the intertidal zone, whereas, kelps are more common in the subtidal zone (Chapman, 1987;Lobban and Harrison, 1994). Fucoids generally have slower decomposition rates than kelps because they have more structural tissue and secondary metabolites that may be toxic to grazers and decomposers (Lobban and Harrison, 1994;Lau and Qian, 1997;Nagayama et al, 2002;Birkemeyer et al, 2020). Because of their slower decomposition, the carbon sequestered by fucoids may therefore have a higher likelihood of naturally being deposited in the deep ocean compared to kelps.…”
Section: Species Selectionmentioning
confidence: 99%
“…To cleave the permethylated phlorotannins of P. canaliculata, polyhydroxy phenols or biphenyls can be obtained by semi-preparative isolation using sodium in liquid ammonia (Glombitza and Klapperich 1985). A portion of phlorotannins is cell wall-bound and in Pelvetia, this proportion is maximal in the receptacles, where phlorotannins may perform a protective role; by contrast, in Fucus the highest proportion of cell wall-bound phlorotannins occurs in the stipe (Birkemeyer et al 2020).…”
Section: Other Constituentsmentioning
confidence: 99%